The effects of migration on poverty and inequality in rural Kosovo - Judith Möllers; Wiebke Meyer (IZA Journal of Labor & Development, 2014)
The economic wellbeing of a large number of rural Kosovar families depends heavily on migrants' remittances. This paper aims at analysing the impact of migration on rural poverty and inequality in Kosovo. It draws on the 2009 nationally representative Kosovo Remittance Study. Analyses are based on a comparison with counterfactual migrant household incomes derived from Propensity Score Matching. We find that remittances have no impact on the extremely poor, but lift around 40% of migrant households above the vulnerability threshold. Gini coefficients show a tendency to increase due to migration. Determinants of different outcomes of migration are explored in a logit regression on migration success. Household and income structure as well as education play a role in how migrant households climb up the income ladder.
Keywords: F22; F24; O15; P36; 330; Migration; Remittances; Poverty; Inequality; Kosovo; Propensity score matching